Relationship between body mass index and oral health indicators: a cross-sectional study - Hamidreza Abdolsamadi; Banafshe Poormoradi; Ghazale Yaghoubi; Maryam Farhadian; Mina Jazaeri (European Journal of Translational Myology, 2023)
Today's prevalence of obesity is dramatically increasing and a two-way interaction between higher body mass index (BMI) and oral health is described in scientific litterature. Accordingly, the present study was aimed to evaluate the relation of BMI and oral health indicators. In this cross-sectional study, 240 individuals according to their BMI were placed in the following experimental groups; underweight (BMI<18), normal weight (18≤BMI≤24.9), overweight (25≤BMI≤29.9) and obese (30≤BMI). Plaque index (PI), gingival index (GI), bleeding on probing (BOP) and decayed, missed and filled teeth (DMFT) were obtained. Data was analyzed by SPSS 26 using descriptive tests and one-way ANOVA at the level of 0.05. The mean age and sex distribution of participants of experimental groups had no significant difference (p>0.05). GI and BOP were significantly lower in normal weight persons than individuals with high BMI (p<0.05). DMFT, the number of decayed, missed and filled teeth was approximately similar in all experimental groups (p>0.05). Pearson correlation coefficient showed a positive significant relation between GI as well as BOP with BMI (p=0.000). Based on the results achieved by the present study, although periodontal health status of overweight and obese individuals was significantly compromised compared to normal weight persons, the dental health status was not affected by BMI.